A new theoretical approach to multilayer adsorption of polyatomics - Romá, Federico José (2005)
The multilayer adsorption isotherms of linear particles (k-mers) on homogeneous surfaces were developed on a generalization in the spirit of the well-known Brunauer-Emmet-Teller's approach. The generalized equation is obtained through an analytical approach that provides the isotherm in the multilayer regime from the isotherm in the monolayer regime. The formalism leads to exact results in one dimension and provides an analytical approximation to study multilayer adsorption on two-dimensional surfaces with different geometries (square, honeycomb and triangular). The entropic effects of the nonspherical character of the adparticles on the determination of the monolayer volume and adsorption energy, are shown and discussed for type II and type III isotherms. Comparison with Monte Carlo simulations in the grand canonical ensemble and experimental adsorption isotherms are used to test the accuracy and reliability of the model. Close agreement between simulated, theoretical and experimental results supports the applicability of the proposed model to describe multilayer adsorption in presence of multisite-occupancy.